Logic-gated and contextual control of immunotherapy for solid tumors: contrasting multi-specific T cell engagers and CAR-T cell therapies - Nolan-Stevaux, Olivier; Smith, Richard (Frontiers in Immunology, 2024)
CAR-T cell and T cell engager therapies have demonstrated transformational efficacy against hematological malignancies, but achieving efficacy in solid tumors has been more challenging, in large part because of on-target/off-tumor toxicities and sub-optimal T cell anti-tumor cytotoxic functions. Here, we discuss engineering solutions that exploit biological properties of solid tumors to overcome these challenges. Using logic gates as a framework, we categorize the numerous approaches that leverage two inputs instead of one to achieve better cancer selectivity or efficacy in solid tumors with dual-input CAR-Ts or multi-specific TCEs. In addition to the “OR gate” and “AND gate” approaches that leverage dual tumor antigen targeting, we also review “contextual AND gate” technologies whereby continuous cancer-selective inputs such a pH, hypoxia, target density, tumor proteases, and immune-suppressive cytokine gradients can be creatively incorporated in therapy designs. We also introduce the notion of “output directionality” to distinguish dual-input strategies that mechanistically impact cancer cell killing or T cell fitness. Finally, we contrast the feasibility and potential benefits of the various approaches using CAR-T and TCE therapeutics and discuss why the promising “IF/THEN” and “NOT” gate types pertain more specifically to CAR-T therapies, but can also succeed by integrating both technologies.